Hubungan Budaya Organisasi dan Komitmen Organisasional pada Kinerja Karyawan - Tanuwibowo, Jessica Clairine; Sutanto, Eddy M. (TRIKONOMIKA, 2014)
The purpose of the research was to find out the relationship of organizational culture and organizational commitment with employee performance. The population in this research were 51 employees at PT Tirta Sarana Sukses. The results found out that organizational culture and organizational commitment were positively related with employee performance. It also showed individually that organizational culture was positively related with employee performance, organizational commitment was positively related with employee performance, and organizational culture was positively related with organizational commitment.